Alessandro Leogrande, La frontiera (Milano, Feltrinelli, 2015, 320 pp. ISBN 978-88-07-88971-4) (Altre Modernità, 2019)
Alessandro Leogrande, La frontiera (Milano, Feltrinelli, 2015, 320 pp. ISBN 978-88-07-88971-4)di Albana Muco